Effect Of Exposure Of Monosadium Glutamate (MSG) on Viability Of Monocyte Cells - Aliza Dewi Fortuna (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
The consumption rate of Monosodium Glutamate (MSG) in Indonesia has increased every year. Uncontrolled use of MSG in Indonesia for a long period of time can cause toxic effects on the body. The free glutamate content produced by MSG can affect the work of the immune system, especially in the innate immune system and cause oxidative stress. To determine the effect of exposure to Monosodium Glutamate (MSG) on the viability of monocyte cells. This study is a laboratory experimental in vitro with a post test only control group design. A total of 10cc of peripheral venous blood was isolated using the ficoll gradient centrifugation method. The results of monocyte cell isolates were exposed to Monosodium Glutamate (MSG) according to groups. Group I: negative control, group II: monocyte cells + MSG 3%, group III: monocyte cells + MSG 6%, group IV: monocyte cells + MSG 9%. Subsequently incubated for 24 hours at 37 °C in 5% CO2. Then the viability test was carried out using trypan blue staining. Monocyte cell viability calculations were carried out under an inverted microscope with a magnification of 400x per 100 cells. The data obtained were analyzed statistically using the one-way Anova test followed by the LSD test. The average viability in each group was obtained as follows, monocyte cell viability in the control group was 63%, group II was 47%, group III was 45% and group IV was 35%. There is an effect of exposure to Monosodium Glutamate (MSG) on the viability of monocyte cells with the most significant effect being the 9% MSG concentration with an average viability of 35%.The consumption rate of Monosodium Glutamate (MSG) in Indonesia has increased every year. Uncontrolled use of MSG in Indonesia for a long period of time can cause toxic effects on the body. The free glutamate content produced by MSG can affect the work of the immune system, especially in the innate immune system and cause oxidative stress. To determine the effect of exposure to Monosodium Glutamate (MSG) on the viability of monocyte cells. This study is a laboratory experimental in vitro with a post test only control group design. A total of 10cc of peripheral venous blood was isolated using the ficoll gradient centrifugation method. The results of monocyte cell isolates were exposed to Monosodium Glutamate (MSG) according to groups. Group I: negative control, group II: monocyte cells + MSG 3%, group III: monocyte cells + MSG 6%, group IV: monocyte cells + MSG 9%. Subsequently incubated for 24 hours at 37 °C in 5% CO2. Then the viability test was carried out using trypan blue staining. Monocyte cell viability calculations were carried out under an inverted microscope with a magnification of 400x per 100 cells. The data obtained were analyzed statistically using the one-way Anova test followed by the LSD test. The average viability in each group was obtained as follows, monocyte cell viability in the control group was 63%, group II was 47%, group III was 45% and group IV was 35%. There is an effect of exposure to Monosodium Glutamate (MSG) on the viability of monocyte cells with the most significant effect being the 9% MSG concentration with an average viability of 35%.